Effects of progressive neuromuscular stabilization exercise on the support surface on patients with high obesity with lumbar instability: A double-blinded randomized controlled trial. Issue 4 (29th January 2021) - Park, Sam-Ho; Lee, Myung-Mo
Abstract: Background: Intensive neuromuscular stabilization exercise on highly obese patients with low back pain results in positive effects of body fat decline and prevention of complications. The purpose of this study is to investigate the effects of progressive neuromuscular stabilization exercise on unstable surface on pain, motor function, psychosocial factors, balance, and abdominal contraction with highly obese patients with lumbar instability. Methods: This study is a double-blinded randomized controlled trial. A total of 46 highly obese patients (body mass index [BMI] ≥ 30 kg/m 2 ) with lumbar instability were assigned randomly to experimental group (n = 23) and control group (n = 23). The control group performed the intensive progressive exercise on a stable surface and the experimental group on an unstable surface. Result: Significant differences were shown for BMI, QVAS, K-ODI, FABQ, and balance ability for both groups before and after the intervention ( P < .05), and only the experimental group showed significant difference for transverse abdominis muscle thickness in contraction and contraction rate ( P < .05). Compared to the control group, the experimental group showed significant difference ( P < .05) in the amount of changes for QVAS, K-ODI, balance ability, transverse abdominis muscle thickness in contraction, and contraction rate. Conclusion: Progressive neuromuscular stabilization exercise program on unstable surfaces demonstrated to be an effective and clinically useful method to decrease pain level, increase motor function, balance, and transverse abdominis muscle thickness in contraction and contraction rate for highly obese patients with lumbar instability.